Campomanesia adamantium and Campomanesia pubesncens are distinct species? Use of palynology and molecular markers in taxonomy - Amaral,Érica Virgínia Estêfane de Jesus (2020)
Abstract The species Campomanesia adamantium and C. pubescens present a great morphological variability, with the existence of morphotypes and the indication of a possible hybridization process occurring between them. Thus, the aim of this study was to characterize the Campomanesia adamantium species and morphotypes of species Campomanesia pubescens through palynological reviews and with the use of molecular markers to assist the taxonomic description of the species. The plant material was collected in the experimental field of Federal University of Jataí, in bloom of 2014, and analyzes were performed in the Morphology Laboratory of Plant Taxonomy and in the Laboratory of Genetics and Plant Breeding belonging to the same institution. Analysis of scanning electron microscopy was performed at the Federal University of Lavras. Important information was found that reinforce the possibility of cross between Campomanesia adamantium and Campomanesia pubescens, generating morphotypes intermediaries, indicating a possible hybridisation process. It can be concluded that Campomanesia adamantium is farthest from the morphotype 2 from Campomanesia pubescens, and morphotypes 1 and 3 are intermediate between them, possibly being hybrids.